Neonatal CD8 T-cell hierarchy is distinct from adults and is influenced by intrinsic T cell properties in respiratory syncytial virus infected mice. - Tracy J Ruckwardt; Allison M W Malloy; Emma Gostick; David A Price; Pradyot Dash; Jennifer L McClaren; Paul G Thomas; Barney S Graham (PLoS Pathogens)
Following respiratory syncytial virus infection of adult CB6F1 hybrid mice, a predictable CD8+ T cell epitope hierarchy is established with a strongly dominant response to a K(d)-restricted peptide (SYIGSINNI) from the M2 protein. The response to K(d)M2(82-90) is ∼5-fold higher than the response to a subdominant epitope from the M protein (NAITNAKII, D(b)M(187-195)). After infection of neonatal mice, a distinctly different epitope hierarchy emerges with codominant responses to K(d)M2(82-90) and D(b)M(187-195). Adoptive transfer of naïve CD8+ T cells from adults into congenic neonates prior to infection indicates that intrinsic CD8+ T cell factors contribute to age-related differences in hierarchy. Epitope-specific precursor frequency differs between adults and neonates and influences, but does not predict the hierarchy following infection. Additionally, dominance of K(d)M2(82-90)-specific cells does not correlate with TdT activity. Epitope-specific Vβ repertoire usage is more restricted and functional avidity is lower in neonatal mice. The neonatal pattern of codominance changes after infection at 10 days of age, and rapidly shifts to the adult pattern of extreme K(d)M2(82-90)-dominance. Thus, the functional properties of T cells are selectively modified by developmental factors in an epitope-specific and age-dependent manner.